2003
DOI: 10.1046/j.1461-0248.2003.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic impacts and historical decline in body size of rocky intertidal gastropods in southern California

Abstract: The diverse fauna and flora of rocky intertidal ecosystems are being impacted by the activities of rapidly increasing coastal populations in many regions of the world. Human harvesting of intertidal species can lead to significant changes in body sizes of these taxa. However, little is known about the temporal trajectories of such size declines and more importantly, the long-term effects of chronic human impacts. Furthermore, it is unclear whether sizes of species not directly targeted for harvesting are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(138 citation statements)
references
References 27 publications
6
121
2
7
Order By: Relevance
“…Present findings have clearly shown that zoo-benthic community are highly sensitive to corresponding human disturbances and disturbances can finally affect on zoo-benthic abundance and growth. Study on historical and field survey data of mainland southern California coast have shown, accompanying with present results that human activities have lead to significant and widespread decline in body size of rocky intertidal gastropod species over the last century (Roy et al, 2003). In contrary to zoobenthos, having lower disturbance index, macroalgae at Rumassala show the higher stress ( Figure 5).…”
Section: Discussionsupporting
confidence: 82%
“…Present findings have clearly shown that zoo-benthic community are highly sensitive to corresponding human disturbances and disturbances can finally affect on zoo-benthic abundance and growth. Study on historical and field survey data of mainland southern California coast have shown, accompanying with present results that human activities have lead to significant and widespread decline in body size of rocky intertidal gastropod species over the last century (Roy et al, 2003). In contrary to zoobenthos, having lower disturbance index, macroalgae at Rumassala show the higher stress ( Figure 5).…”
Section: Discussionsupporting
confidence: 82%
“…Of these, 14 shells spanning the period 40-19 kyrs BP were analysed to produce oxygen isotope profiles and 10 of these were analysed to produce Mg/Ca ratio profiles. Historical and contemporary empirical data from sites around the world have often shown reductions in body size in Patella and similar species through time (Keough et al, 1993;Roy et al, 2003). A significant, although not the sole, contributor to this observed size reduction has been the sustained exploitation of these species over time by humans for food or fish bait.…”
Section: Shell Sampling and Micromillingmentioning
confidence: 99%
“…Archaeological middens the world over demonstrate that coastal shellfish have been harvested for hundreds of years to millennia [11][12][13] and have undergone marked changes to their ecological structure as a result [14][15][16][17][18][19]. Many (but not all) mollusc species that have a long history of subsistence harvesting have become smaller over time [14,16,20], suggestive of size-selective evolutionary change.…”
Section: Introductionmentioning
confidence: 99%
“…Many (but not all) mollusc species that have a long history of subsistence harvesting have become smaller over time [14,16,20], suggestive of size-selective evolutionary change. It is impossible, however, to convincingly establish if the causal mechanism is selection to mature at a smaller size, as described above, or if it is simply because larger individuals become less common as they are preferentially harvested, thereby lowering mean size.…”
Section: Introductionmentioning
confidence: 99%